(untitled) (Research, Society and Development, 2026)
Lipedema is a chronic and progressive disease characterized by bilateral fat accumulation in the lower and/or upper limbs, primarily affecting women during periods of hormonal fluctuation, such as puberty, pregnancy, and menopause. The main symptoms include pain, edema, and bruising. Its pathophysiology is not yet fully understood, although estrogen is hypothesized to play a role in disproportionate fat accumulation. Lipedema is often underdiagnosed due to its similarity with obesity, cellulite, and lymphedema, which can delay treatment. Nutritional management, including ketogenic, Mediterranean, and low-carbohydrate diets, may help reduce disease progression. This study aims to evaluate different dietary approaches in the management of lipedema based on its pathophysiology, through an integrative literature review. Articles published in the last five years were searched in databases such as PubMed, SciELO, MDPI, and Google Scholar, using the descriptors “Lipedema,” “Nutritional Therapy,” and “Pathophysiology”.